Analysis Of The Influence Of Economic Growth, Open Unemployment Rate, And The Percentage Of Poor Population Towards HDI North Sumatera City Regency, 2010 - 2022 - Purba, Elvis Fresly; Nopeline, Nancy; Lastri, Lastri; Gea, Putri Anjelina Anjelina (LPPM Universitas PGRI Sumatera Barat, 2024)
One of the indicators of the success of the development of a country, province, district or city is the human development index (HDI), because it can describe the success of building the quality of human life. This index is not only useful for determining the development ranking but is also strategic data to measure government performance and is also one of the allocators for determining the General Allocation Fund (DAU) from the central government to the regions. The purpose of this study was to determine the effect of economic growth, open unemployment rate, and percentage of poor population on the HDI of regencies/cities in North Sumatra Province. The data analyzed were panel data which were a combination of cross-section data (25 regencies and 8 cities) and time series ( 2010-2022 ) obtained from the publication of the Central Statistics Agency (BPS) of North Sumatra Province. The data were analyzed using Eviews version 12.0. Based on the data analysis, the best panel data regression model was the Fixed Effect Model (FEM). Based on the partial test (t-test), the open unemployment rate and percentage of poor population had a negative and significant effect on the HDI and were in accordance with theoretical expectations. On the other hand, the effect of economic growth was not in accordance with theoretical expectations because its effect was negative and significant on the HDI. This shows that economic growth is not necessarily a panacea for overcoming the problems of unemployment and poverty. In other words, increasing economic growth cannot automatically increase the purchasing power of the population of regencies/cities in North Sumatra Province. Furthermore, the simultaneous test showed that the three independent variables had a significant effect on the HDI. The coefficient of determination of the panel data regression model is 88.89 percent, which means that there are still other independent variables that can explain the variation in HDI, although only 11.11 percent.